1992
DOI: 10.1007/bf03192222
|View full text |Cite
|
Sign up to set email alerts
|

The effect of roasting on the fate of aflatoxin B1 in artificially contaminated green coffee beans

Abstract: A study was undertaken to evaluate aflatoxin B1 contamination in coffee beans. 41 samples of green coffee were collected from large lots of material by representative sampling. The raw samples were analyzed and showed no detectable levels of aflatoxin B1. In order to establish the heat stability of the toxin, 3 artificially contaminated samples (average level 10/μg/kg) were roasted atca 200°C for different operation times periods so as to reproduce light and dark roasting procedures. Each sample was roasted bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…Effect on AFs levels. The roasting conditions such as temperature and duration play significant role in reducing the mycotoxins contents in coffee beans [35][36][37]. In the present study, roasting coffee beans at three traditional methods significantly reduced AFs contents in the naturally contaminated samples (Fig 3).…”
Section: Plos Onementioning
confidence: 51%
“…Effect on AFs levels. The roasting conditions such as temperature and duration play significant role in reducing the mycotoxins contents in coffee beans [35][36][37]. In the present study, roasting coffee beans at three traditional methods significantly reduced AFs contents in the naturally contaminated samples (Fig 3).…”
Section: Plos Onementioning
confidence: 51%
“…A cafeína (1,3,7 trimetilxantina) constitui componente natural em café, com atividade fungistática e efeito antimicotoxigênico simultâneo (Buchanan et al 1983). Este composto pode atuar como agente protetor contra a produção de afl atoxina B1 em grãos de café, mesmo em condições climáticas favoráveis ao crescimento do fungo produtor (Micco et al 1992). O mesmo pode ter ocorrido para ocratoxina A nas condições deste estudo.…”
Section: Resultsunclassified
“…A study by Micco et al. (1992) found that roasting reduces aflatoxin levels in coffee beans. Different reduction levels have been reported.…”
Section: Agricultural Products and Foods Contaminated By Aflatoxinsmentioning
confidence: 99%